Trajetórias de mulheres negras líderes de movimentos sociais em Araraquara - SP: estratégias sociais na construção do modo de vida - Silva, Maria Aparecida (2011)
This thesis is about the experience of black women living in two different neighbourhoods of Araraquara, state of São Paulo, named Santana and Vila Xavier, who take part in the Black social movement, organizing cultural events or who attend a mainly afro-Brazilian environment. This research is qualitative and starts in the 1970s and ends 2010. Interviews were used as a methodological tool to collect the data featuring orally handed down history. Based on the interviews with 21 black women, their social environment, their insertion into the mainly afro-Brazilian community, the importance of education and schooling, and the significance of their areas of influence and action were reconstructed. The aim of this research is to verify, unveil and understand the social strategies elaborated by these women based on their experience by constructing a way of life that contributes to the strengthening of their identity, their development and performance in the Black social movement. These concerns arise as a way to broaden the comprehension of how this part of the population is perceived by a society that has defined its social roles. Roles that are in a sort of way subtly imposed and absorbed as a mean, by which social relationships are built and maintained. The approach is based on three main points of discussion: gender, ethnic-racial and black social movement. As the research is focused on women it’s inconceivable not to address the differences such as the relationship of power between sexes, and given they are black women, the ethnic-racial discussion about discrimination, particularities and singularities is possible but also the black social movement as a path to education, training and empowerment as a leader. Making them visible is to rescue them from the margins of society and to build a new history.